Performance Optimization of Staff in Improving Guest Satisfaction - Ni Wayan Mega Sari Apri Yani; Putu Eka Wirawan (Universitas Pendidikan Ganesha, 2022)
During the Covid-19 pandemic, Bali tourism experienced difficult times, so that many businesses in the tourism accommodation sector were destroyed. Various efforts were made, so that they could survive in difficult times, one of which was strict financial arrangements, reduction of employees, laying off and laying off employees. The performance of the waiter plays an important role in the smooth operation of a restaurant, so it is necessary to optimize the performance of the waiter so that guest satisfaction increases. At the Warung Mesari restaurant, the waiter is not only a waiter for visiting guests, but also an ambassador in introducing and maintaining the restaurant's image. This study looks at the performance of waiters in an effort to increase guest satisfaction and what efforts are made by the Warung Mesari restaurant in optimizing the performance of the waiters. The research method used is descriptive-qualitative with data collection techniques in the form of interviews, documentation studies, and observations. This study resulted in the following findings: the waiters were able to provide good service and establish good relationships with guests who visited the restaurant; the waiters have done their job successfully; the restaurant has received many positive guest comments from guests; the restaurant also gets repeater guests; and guests who have visited again invite their friends to visit the Warung Mesari restaurant.